Analyzing the Groundwater Contamination - Central Basin - Erbil City Kurdistan Region -Iraq - Noor Khalid Yousif Yahooa; Dana Khider Mawlood (Zanco Journal of Pure and Applied Sciences, 2023)
Groundwater is one of the most crucial drinking water sources in Kurdistan. Development, urbanization, and human activities in Erbil have led to a decline in the amount and quality of groundwater. This research aims to investigate and examine the groundwater quality in Kaniqrzhala (Erbil dumpsite) in a central basin in Erbil, as well as the impact of a landfill in this region. The investigation encompasses around 27 wells. The static water level is assessed to examine groundwater movement and the route of contaminant transfer. All the wells are sampled for groundwater quality criteria such as turbidity (pH value, TDS, chloride, calcium, magnesium, hardness, nitrate, sodium, iron, and copper). Surfer software version (16) was used to study the direction of groundwater flow; groundwater contamination was investigated using the GIS program version (10.6.1). The result showed the groundwater flow toward the Greater Zab River; many wells suffer from high contamination. The effect of landfill appears in this area. Groundwater contamination transport in the Kaniqurzala should be studied to predict the future impact using modeling software.